Innovative approaches to biohydrogen production from organic waste: pathways and sustainability challenges - Mobina Rostampour Gabanki; Hossein Yousefi; Ahmad Hajinezhad; Mahmood Abdoos; Shayan Mohammaddini (Waste Management Bulletin, 2025)
Biohydrogen production from organic waste offers a sustainable alternative to fossil fuel-derived hydrogen, contributing to the transition toward clean energy. This study explores advancements in microbial engineering, hybrid fermentation, and reactor optimization to enhance hydrogen yields and process efficiency. The objective is to develop innovative biohydrogen production methods that maximize substrate conversion efficiency while ensuring economic feasibility. Key innovations includenanoparticle-assisted hydrogenase activation, and hybrid fermentation integrating dark fermentation with microbial electrolysis cells (MECs) and photofermentation. Advanced continuous stirred tank reactors (CSTRs) and packed-bed bioreactors significantly improve hydrogen production. Results show hydrogen yields of 20–50 L H2/kg volatile solids (VS), with optimized systems increasing conversion efficiency by up to 35 %. Aspen HYSYS modeling identifies peak production at pH 5 and mesophilic temperatures (35–40 °C). A SimaPro-based life cycle assessment (LCA) reveals a global warming potential (GWP) reduction of −1.2E3 kg CO2 per ton of MSW and a resource impact benefit of −67 USD per ton, demonstrating economic feasibility. This study supports biohydrogen’s scalability as a waste-to-energy solution, aligning with circular bioeconomy principles. Future research should focus on microbial robustness, hybrid biorefineries, and AI-driven process control for enhanced sustainability. The findings position biohydrogen as a cost-effective and environmentally friendly clean energy source, accelerating global decarbonization efforts.